Kajian Literatur: Aplikasi Sejumlah Metode Ekstraksi Konvensional untuk Mengekstraksi Senyawa Fenolik dari Bahan Alam - Arrofiqi, Mochammad Rasyad; Sakti, Aditya Sindu; Mayangsari, Fransisca Dita (Jurnal Penelitian Farmasi Dan Herbal, 2024)
This literature review explores various conventional extraction methods utilized to extract phenolic compounds from natural materials. Phenolic compounds, known for their significant antioxidant, anti-inflammatory, and anticancer properties, are crucial bioactive molecules found in plants. The study examines methods such as maceration, percolation, reflux, Soxhlet, digestion, infusion, and decoction, highlighting their efficiencies, advantages, and limitations. The findings suggest that while conventional methods are cost-effective and accessible, they often require longer extraction times and may lead to thermal degradation of sensitive compounds